2023
DOI: 10.1590/1806-9282.20221295
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic heart rate modulation in patients with coronavirus disease 2019 in mechanical ventilation

Abstract: BACKGROUND: Patients with coronavirus disease 2019 on automatic mechanical ventilation have greater heart rate modulation with greater parasympathetic modulation. OBJECTIVE: To analyze the autonomic modulation of heart rate in critically ill patients with coronavirus disease 2019 on invasive mechanical ventilation. METHODS: A cross-section study was carried out with 36 individuals divided into two groups. The control group included patients of both genders, in orotracheal intubation with invasive mechanical ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…In contrast to our study, a study of patients with COVID-19 infection and mechanical ventilation reported a greater parasympathetic modulation of heart rate, as evidenced by higher levels of pNN50 and rMSSD compared with patients without COVID-19 infection, and the author concluded that the monitoring of parasympathetic tone in COVID-19 infection may be a predictive marker of disease progression (39). In another study of patients with severe head injury, increased parasympathetic tone assessed by HRV on the day after trauma was predictive of brain death, whereas a decreased parasympathetic tone in the awakening period was associated with worse clinical recovery, suggesting a dynamic change in autonomic nervous tone in these patients (40).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our study, a study of patients with COVID-19 infection and mechanical ventilation reported a greater parasympathetic modulation of heart rate, as evidenced by higher levels of pNN50 and rMSSD compared with patients without COVID-19 infection, and the author concluded that the monitoring of parasympathetic tone in COVID-19 infection may be a predictive marker of disease progression (39). In another study of patients with severe head injury, increased parasympathetic tone assessed by HRV on the day after trauma was predictive of brain death, whereas a decreased parasympathetic tone in the awakening period was associated with worse clinical recovery, suggesting a dynamic change in autonomic nervous tone in these patients (40).…”
Section: Discussioncontrasting
confidence: 99%
“…The clinical implications of increased parasympathetic tone in intensive care medicine have been less reported in the literature. A study of patients with COVID-19 infection and mechanical ventilation reported a greater parasympathetic modulation of heart rate, as evidenced by higher levels of pNN50 and rMSSD compared with patients without COVID-19 infection, and the author concluded that the monitoring of parasympathetic tone in COVID-19 infection may be a predictive marker of disease progression [28]. In another study of patients with severe head injury, increased parasympathetic tone assessed by HRV on the day after trauma was predictive of brain death, whereas a decreased parasympathetic tone in the awakening period was associated with worse clinical recovery, suggesting a dynamic change in autonomic nervous tone in these patients[29].…”
Section: Discussionmentioning
confidence: 99%